عملية غسيل الاموال ابرز المضامين و سبل المعالجة (المجلة العراقية للعلوم الاقتصادية, 2018)
Lawyers and Bankers agreed that washing funds Considered as a crime? … Information technology, the electronic transfers of funds and Globalization. all play important role in its development…Whether we consider this action as crime or not ? and how can we minimized its effects ?that is the main theme of this paper